Contribuciones a la generalización del problema de compensación por grupos de Helmert-Pranis Pranievich - Popescu, Ioan (Revista Matemática Complutense, 1988)
. The papa presents in a generalized form the problem of the geodetic network adjustment by the Helmert-Pranis Pranievich &ouP method (groups with junction points included or not). The adjustment problem, as well as the cobactor matrix derivation for the partialindependent and linkage unknowns, was completely formulated by transformed weight matrix deftnition and usage. A complete sequence of the computing stages for <he geodetic networks divided into groups without junction points was given for efacient programming of adjustment ptocessing on computer. A practical example illustrates the identity of the solutions and the cofactors obtained by <he group adjustment proposed to those obíained by the block adjustment.